Program Peningkatkan Kualitas Baca Al-Qur’an Melalui Halaqoh Sinau Tajwid (HST) Santri TPQ Riyadhotul Ulum Kencong Kepung Kediri - Tamaniyatun Nada; Rohmad (LP3M IAIFA Kediri, 2021)
The social environment of today's society that begins to minimally support religious activities in the afternoon that used to always be favoured makes children gradually begin to experience a lag in terms of religion. Therefore, this mentoring activity is carried out and focused on strengthening the child's religion through halaqah sinau tajwid. This community assistance activity is considered successful in waking the community to the existence that occurs in its environment. In this mentoring activity, researchers and the community also build good communication and cooperation by supporting their daughter's son to participate in halaqah sinau tajwid activities. The activeness of learners in learning activities and the ability to read the Qur'an better for children can make the benchmark of learning success halaqah sinau tajwid. The success of this program can also be made into a model of implementation of religious strengthening in other areas by matching existing conditions.